ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF TAMSULOSIN AND TOLTERDOINE IN BULK & PHARMACEUTICAL DOSAGE FORM BY RP-HPLC METHOD - B. Siddartha; Sudheer Babu, I.; Ravichandra Gupta, Ch.; Parthiban, C. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
A simple, specific and accurate reverse phase high performance liquid chromatographic method was developed for the simultaneous determination tamsulosin and tolterodine in pharmaceutical dosage form. The column used was Hypersil BDS C18, 100 x 4.6 mm, 5m in isocratic mode, with mobile phase containing phosphate buffer and acetonitrile (65:35 v/v) adjusted to pH 3.8 with dilute ortho phosphoric acid solution. The flow rate was 1.0 ml/ min and effluents were monitored at 220 nm. The retention times of tamsulosin and tolterodine were found to be 2.285 min and 4.334 min, respectively. The linearity for tamsulosin and tolterodine were in the range of 1-6 µg/ml and 10-60 µg/ml respectively. The recoveries of tamsulosin and tolterodine were found to be 98.40 to 100.42% and 98.16 to 99.76%, respectively. The proposed method was validated and successfully applied to the estimation of tamsulosin and tolterodine in combined tablet dosage forms.